Numerical investigation on the thermal performance of parabolic trough solar collector with synthetic oil/Cu nanofluids. (5th June 2023) - Dou, Lizhuang; Ding, Bin; Zhang, Qiang; Kou, Guiyue; Mu, Mingfei
Highlights: Thermal performance of the PTC with nanofluids are numerically revealed. The CTD is greatly reduced with the help of synthetic oil/Cu nanofluids. A lower flow rate and higher inlet temperature lead to higher efficiency increment. Syltherm 800 is more suitable for being the base fluid in terms of efficiency improvement. Abstract: Nanofluids as the advanced heat transfer fluids, could be used in the parabolic trough solar collector system because of the enhanced thermal transport properties. In this paper, the effects of the same nanoparticles with two different base fluids on the thermal performance of the collector are numerically investigated by finite element method. Moreover, the effect of nanofluids on the cross-sectional temperature distribution of the absorber tube, which is well-known to affect the collector performance is here investigated. The numerical study is divided into two groups according to the value range of inlet velocity and inlet temperature, which represents different application scenarios of the collector. The results show that the synthetic oil/Cu nanofluids could increase the convective heat transfer coefficient under wide working conditions, but more pumping work is required because of the increase in pressure drop. The cross-sectional temperature difference of the absorber tube is greatly decreased with synthetic oil/Cu nanofluids. Furthermore, it's found that Cu nanoparticles could trigger thermal and exergetic efficiency increment, especially at a low flow rate and high working temperature. The thermal performance improvement of these two thermal oils by Cu nanoparticles is different, and Syltherm 800 is more suitable for being the base fluid of nanofluid.